Answer:
y-1=2(x+4) or y=2x+9
Step-by-step explanation:
y - 3 = 2(x + 7)
y=mx+b
m=2
(x1,y1) -> (-4, 1)
(y−y1)=m(x−x1)
plug in
y-1=2(x+4)
y-1=2x+8
y=2x+9
test:
(1)=2(-4)+9
1=-8+9
1=1
Answer:
I figure you could simplify it by multiplying both sides by 6, resulting in -31+23=-30+18-1+5
-8=-8
Step-by-step explanation:
Answer:
Alright well solve for z by simplifying by both sides of the equation, then isolating the variable
Exact form: z = 2/5
Decimal form: o.4 Hope this helps :)
Step-by-step explanation:
Answer:
The second graph
Step-by-step explanation: